Trends in Systemic Lupus Erythematous Mortality in the United States, 1999–2022 - Sagar Patel; Joseph Bettag; Nikita Baral; Abubakar Tauseef; Ali Bin Abdul Jabbar (ACR Open Rheumatology, 2025)
Objective Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with variable mortality rates among different demographic groups. Despite treatment advancements, disparities in SLE outcomes continue to exist. Methods This study used the Centers for Disease Control and Prevention Wide‐ranging Online Data for Epidemiologic Research database data from 1999 to 2022 to examine SLE‐related mortality trends. Age‐adjusted mortality rates (AAMRs) were calculated, and Joinpoint regression was employed to evaluate annual percentage changes (APCs) over time for mortality stratified by gender, race, census regions, age groups, and states. Results A total of 52,430 SLE‐related deaths occurred over the study period. The AAMR decreased from 1 per 100,000 in 1999 to 0.78 per 100,000 in 2022. The AAMR of SLE‐related deaths decreased by 21% from 1 in 1999 to 0.79 in 2019 (average APC −1.23, 95% confidence interval −1.48 to −0.96). It increased by 21.52% from 0.79 in 2019 to 0.96 in 2021. From 1999 to 2019, men decreased by 33.33% compared to 21.02% in women, whereas women saw a more considerable increase from 2019 to 2021. Non‐Hispanic Asians or Pacific Islander patients saw the most decrease (−43.37%), followed by Hispanic patients (−40.60%), non‐Hispanic African American patients (−25.83%), and non‐Hispanic White patients (−21.43%). Hispanic patients saw the most significant increase from 2019 to 2021, whereas non‐Hispanic African American patients had the highest AAMR among all racial and ethnic subgroups from 1999 to 2022. The South had the highest AAMR throughout the study period among census regions. Conclusion Persistent disparities have been observed in SLE‐related mortality rates from 1999 to 2022, with female sex, non‐Hispanic African American race, and southern region being disproportionately impacted by worse mortality outcomes.